Metastatic lung adenocarcinoma to the oral cavity/ Mohd Naqiuddin Mohd Najib ... [et al.] - Mohd Najib, Mohd Naqiuddin; Abu Bakar, Muhammad Nasri; Hashim, Hasme Zam; Mohamad, Irfan (Faculty of Medicine, 2023)
Primary oral neoplasms are relatively common. They tend to have positive neck adenopathy at presentation. Metastatic deposits are rare, and mainly reported to the soft tissue of the oral cavity and to the jawbones. The possible primaries include gastrointestinal and genitourinary tracts. We report a case of an oral cavity mass with initial complaint of toothache and neck swelling with multiple neck nodes. Biopsies taken from the left retromolar trigone and supraclavicular lymph node revealed poorly differentiated metastatic adenocarcinoma. Computed tomography scan suggested primary lung cancer. Early detection of lung cancer should be the clinician's concern. The presence of an oral mass already indicates a late stage of lung cancer with poor prognosis.